Evaluation of the Operational CMEMS and Coastal Downstream Ocean Forecasting Services During the Storm Gloria (January 2020) - Sotillo, Marcos G.; Mourre, Baptiste; Mestres, Marc; Lorente, Pablo; Aznar, Roland; García-León, Manuel; Liste, Maria; Santana, Alex; Espino, Manuel; Álvarez, Enrique (Frontiers in Marine Science, 2021)
Storm Gloria was the 10th named storm in Europe for the 2019–2020 winter season, and it severely affected Spain and France. This powerful storm represents an excellent study case to analyze the capabilities of the different ocean model systems available in the Spanish Mediterranean coasts to simulate extreme events, as well as to assess their suitability to enhance preparedness in maritime disasters with high impacts on coastal areas. Five different operational ocean forecasting services able to predict the storm-induced ocean circulation are evaluated. Three of the systems are delivered by the Copernicus Marine Service (hereafter CMEMS): the CMEMS global scale solution (GLO-1/12°), the specific Mediterranean basin scale one (MED-1/24°), and the regional solution for the Atlantic façade (IBI-1/36°), which includes also part of the western Mediterranean. These CMEMS core products are complemented with two higher resolution models focused on more limited areas, which provide operational forecasts for coastal applications: the WMOP system developed at the Balearic Islands Coastal Observing and Forecasting System (SOCIB) with a horizontal resolution of roughly 2 km and the Puertos del Estado (PdE) SAMOA systems with a 350-m resolution that cover the coastal domains of the Spanish Port Authorities of Barcelona, Tarragona, Castellón and Almeria. Both the WMOP and SAMOA models are nested in CMEMS regional systems (MED and IBI, respectively) and constitute good examples of coastal-scale-oriented CMEMS downstream services. The skill of these five ocean models in reproducing the surface dynamics in the area during Gloria is evaluated using met-ocean in situ measurements from numerous buoys (moored in coastal and open waters) and coastal meteorological stations as a reference to track the effects of the storm in essential ocean variables such as surface current, water temperature, and salinity throughout January 2020. Furthermore, modeled surface dynamics are validated against hourly surface current fields from the two high-frequency radar systems available in the zone (the SOCIB HF-Radar system covering the eastern part of the Ibiza Channel and the PdE one at Tarragona, which covers the Ebro Delta, one of the coastal areas most impacted by Gloria). The results assess the performance of the dynamical downscaling at two different levels: first, within the own CMEMS service (with their regional products, as enhanced solutions with respect to the global one) and second in the coastal down-streaming service side (with very high-resolution models reaching coastal scales). This multi-model study case focused on Storm Gloria has allowed to identify some strengths and limitations of the systems currently in operations, and it can help outlining future model service upgrades aimed at better forecasting extreme coastal events.